Estimasi Bayes pada Distribusi Pareto dengan Data Tersensor Tipe II - Atika Ahmad; Nonong Amalita (Journal of Mathematics UNP, 2018)
Abstract Parameter’s estimation is used to estimate the parameter values of a discrete distribution as well as a continuous distribution. One form of continuous distribution is the Pareto distribution, where the Pareto distribution has parameters, they are theta dan lambda. The method used to estimate parameters is Bayes estimation. Bayes Estimation has its own way of determining the initial distribution form (prior) and posterior distribution. Parameter’s estimations are also used in one statistical analysis technique that investigates the survival of an  product or individual. The life test data used is type II censored data where the experiment will be stopped after getting r data. This reseach aims to determine the form of parameter estimators and in the Pareto distribution on type II censored data using Bayes estimation. The results in this reseach obtained the form of posterior distribution from Pareto distribution on type II censored data and form of estimator theta dan lambda.